Clive Walker. Terrorism and the Law - Amos N. Guiora (Perspectives on Terrorism, 2012)
Oxford: University Press, 2011. 720 pages; ISBN 13: 978-0-19-956117-9 & ISBN10: 0-19-956117-6. US $ 300.-/ £ 145.- (Hardback). Reviewed by Amos N. Guiora.